Reviews of new publications - Lambert, Frank (KUKILA, 2006)
Handbook of the Birds of the World, Volume 9: Cotingas to Wagtails. del Hoyo, J., Elliott, A. and Christie, D. (eds). Lynx Edicions Handbook of the Birds of the World, Volume 10: Cuckoo-shrikes to Thrushes. del Hoyo, J., Elliott, A. and Christie, D. (eds) . Lynx Edicions